Fabrication of yttria-doped barium zirconate electrolyte with sub-micrometer thickness via low temperature viscous flow sintering - Biswas, Mridula (2017)
Viscous flow sintering strategy has been adopted to obtain dense sub-micrometer thin yttria-doped barium zirconate (BZY) films fabricated via chemical solution deposition method. Viscous flow sintering was carried out at the temperatures between 475 and 575 °C for 24 h to allow densification in amorphous phase so as to avoid coarsening. The sintered films were finally heat treated at 950 °C for 2 h to eliminate the pores generated due to the removal of residual carbon which remains after low temperature viscous flow sintering. Dense, single-phase perovskite BZY films with thickness between 325 and 375 nm were obtained without the presence of barium carbonate, which is a common issue associated with soft chemical synthesis of BZY. In addition to this, this process does not require sintering aid.